Analysis of Bandung City Muzaki Satisfaction with the Services of the National Amil Zakat Agency (BAZNAS) - Yudi Haryadi; Wasifah Hanim; Siti Mardiana; Molly Mustikasari; Aprilian Dheabella Valentino (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The National Amil Zakat Agency in Indonesian “Badan Amil Zakat Nasional” (BAZNAS) in Bandung City places a high priority on measuring muzakki satisfaction in all aspects of service delivery. In order to increase the muzakki's (those who pay zakat) trust in BAZNAS in Bandung City, it is obvious that service improvement is required. This study has a descriptive study design and a quantitative methodology. Its goals are to assess the level of community satisfaction with the services supplied by the local institution, explain and comprehend the quality of services offered, and gauge how closely community satisfaction corresponds to the institution's actual performance of services. Purposive sampling is the method of sampling that was used, and 344 respondents made up the sample. The measurement method for the public service satisfaction index and the calculation described in the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 regarding Guidelines for Preparing Public Service Organizer Satisfaction Surveys and SERVQUAL are combined in the analysis method used to calculate the muzakki satisfaction index for BAZNAS in Bandung City. 90% of the muzakki express concern and high concern for BAZNAS activities, despite the fact that they have no direct interaction with BAZNAS in Bandung City, according to an analysis of muzakki perceptions of zakat administration by BAZNAS in that city. 50.56% of the muzakki reported that the “Unit Pengumpul Zakat” UPZ (collecting and distribution units) at their individual universities are how they find out about BAZNAS initiatives. Information is accessed by the remaining 49.49% of the muzakki via various digital channels. About 60% of the muzakki in Bandung City believe that BAZNAS' official website and social media pages are "informative" in how they publish their activity reports. 85% of the muzakki in Bandung say that the needy and poor groups should be the focus of the zakat distribution carried out by BAZNAS. Bandung Sehat, Bandung Taqwa, Bandung Makmur, Bandung Cerdas, and Bandung Peduli are the five BAZNAS projects in Bandung City that earn the maximum support from the muzakki, each receiving 43.56%. Almost all of the components (indicators) of the muzakki satisfaction measurement fall into the "good" category, scoring between 3 and 4. Only one indication receives a score of 4.01 or above, which is in the trust area and represents a very good result. One more indication, rating 3.69 (good), is above 4.00 in the satisfaction category. The Bandung City Muzakki's impression of service quality was used to calculate the BAZNAS Service Quality Index, and the outcome is 77.03. In general, the muzakki rate the zakat management and distribution services offered by BAZNAS in Bandung City as being pretty satisfactory.